MORALITAS ASKETISME SYEKH SITI JENAR: STUDI TRILOGI SYEKH SITI JENAR KARYA AGUS SUNYOTO - Sujadi, Agus (Balai Bahasa Jawa Timur, 2017)
Sheikh Siti Jenar is a sensational figure through his teachings that are monotheistic. It is not so when reading the novel trilogy by Agus Sunyoto. The spiritual aspects of religion, which are presented can be said to be logical when viewed through the angle of asceticism. Research studies conducted in the form of text with the approach of critical discourse analysis (CDA). The data collected from the text unit of the novel trilogy of Sheikh Siti Jenar by Agus Sunyoto. The result of this research is, asceticism as individual morale leads to social and political morale. And the ascetic ethos of Sheikh Siti Jenar as a human person provides the impetus and limitation to act in his daily behavior. So the ascetic morality of Sheikh Siti Jenar has a general and expansive character.